If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) = 5(3x + -7) + -3(x + 2) Reorder the terms: 2(4 + x) = 5(3x + -7) + -3(x + 2) (4 * 2 + x * 2) = 5(3x + -7) + -3(x + 2) (8 + 2x) = 5(3x + -7) + -3(x + 2) Reorder the terms: 8 + 2x = 5(-7 + 3x) + -3(x + 2) 8 + 2x = (-7 * 5 + 3x * 5) + -3(x + 2) 8 + 2x = (-35 + 15x) + -3(x + 2) Reorder the terms: 8 + 2x = -35 + 15x + -3(2 + x) 8 + 2x = -35 + 15x + (2 * -3 + x * -3) 8 + 2x = -35 + 15x + (-6 + -3x) Reorder the terms: 8 + 2x = -35 + -6 + 15x + -3x Combine like terms: -35 + -6 = -41 8 + 2x = -41 + 15x + -3x Combine like terms: 15x + -3x = 12x 8 + 2x = -41 + 12x Solving 8 + 2x = -41 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 8 + 2x + -12x = -41 + 12x + -12x Combine like terms: 2x + -12x = -10x 8 + -10x = -41 + 12x + -12x Combine like terms: 12x + -12x = 0 8 + -10x = -41 + 0 8 + -10x = -41 Add '-8' to each side of the equation. 8 + -8 + -10x = -41 + -8 Combine like terms: 8 + -8 = 0 0 + -10x = -41 + -8 -10x = -41 + -8 Combine like terms: -41 + -8 = -49 -10x = -49 Divide each side by '-10'. x = 4.9 Simplifying x = 4.9
| 7(2x-8)=8 | | 7y-2 | | -44-92=31-3z | | -4y+10=-2(3y+2) | | 20+x=7 | | (2x-9)+(1.5x+6)=32 | | ln(x)=2ln(3)+ln(5) | | 4(x-6)=3x+16 | | 2(x-1)-7x=18-5(x+4) | | 4=-2h+9 | | 2m=1 | | 4x+7=1x-2 | | 2(x-1)17x=18-5(x+4) | | 9(x-2)/3=27 | | .25(-x-8)=45 | | 5(x+-7)=-45 | | 2x+5-2x^2-3x= | | 7y-2(8+1)=4 | | x+r=9 | | 500-15w=200+12w | | 6-20=24 | | 5+4x=41x | | 6(x-4)=24-2x | | 5x+11=20+2x | | 10x-15=8x+14 | | -96-10x=9x+16 | | 2x-6=39-7x | | -a+(3a)+15+15a-(-2)= | | 4(x-6)-8=-32 | | 0=16t^2+20t-20 | | 100n+2=902 | | 5+14s-2=9s+99-7s |